ASPEK KEADABAN DALAM MASYARAKAT MADANI * EKSPLORASI AWAL GAGASAN INTELEKTUAL MUSLIM - Arifin, Syamsul (Jurnal Bestari, 2001)
In precent time, civil society become important subject to be disscused. In indonesia, civil society (called Madani Society ) find relevant discourse, especially, in the term of modern moslem intelecluals thinking. There is a closed relation between civil society in general to the ?ummah concept? in the Holy Qur?an that has been conducted by islam is Madinah. The similarity of the two concepts, as a sample, are on the human-emansipation, otonomyfor society, political participations, free public sphere, pluralism, etc.